2019
DOI: 10.1186/s12978-019-0742-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obstetric and socio-demographic determinants of low birth weight: a retrospective cross-sectional study in Ghana

Abstract: Background Birth weight is an important predictor of early neonatal mortality, morbidity, and long-term health outcomes. Annually, approximately 20 million babies are born globally with weights less than 2.5kg. In sub-Saharan Africa, the prevalence of LBW is around 13 to 15 percent. In Ghana, 10% of babies born in 2014 were with LBW. The aim of this study was to identify maternal socio-demographic and obstetric risk factors associated with the birth weight of newborns in the Sunyani Municipality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 29 publications
(34 reference statements)
8
29
1
5
Order By: Relevance
“…Literate mothers were 68% less likely to have low weight babies compared to their illiterate counterpart. is finding is consistent with other studies where literate mothers were found to have a protective effect against LBW [18][19][20][21]. Mothers involved in labor work were five times and mothers who were unemployed or housewives were two times more likely to deliver LBW baby than the employed counterpart.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Literate mothers were 68% less likely to have low weight babies compared to their illiterate counterpart. is finding is consistent with other studies where literate mothers were found to have a protective effect against LBW [18][19][20][21]. Mothers involved in labor work were five times and mothers who were unemployed or housewives were two times more likely to deliver LBW baby than the employed counterpart.…”
Section: Discussionsupporting
confidence: 92%
“…Regular ANC during pregnancy is beneficial for both the pregnant mother and developing baby as obstetric complications can be identified during ANC and managed timely [18]. Studies conducted in Malawi and Uganda [39], Ethiopia [29], and Bangladesh [40] have identified an inadequate number of ANC visits to be associated with higher odds of LBW.…”
Section: Discussionmentioning
confidence: 99%
“…However, this nding was incongruent with a similar study conducted in the Brong-Ahafo region of Ghana. That literature suggested that increasing parity signi cantly increased the odds of low birthweight (30). Another study in Ethiopia reported similar ndings to those of Mohammed and colleagues (31).…”
Section: Discussionsupporting
confidence: 75%
“…Although there is evidence of increasing birth weight in some developing countries [25], ABW is an under-researched child health topic in urban Africa. Most studies on birth weight in Africa have focused on low birth weight, with risk factors including maternal and child characteristics, healthcare utilization, household, nutrition, environment and community variables [14,[31][32][33][34][35][36]. On the contrary, studies on high birth weight in Africa have been few, but available evidence shows that the significant risk factors are maternal obesity, socioeconomic condition, residence and gestational diabetes [22,[37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%